2017
DOI: 10.7861/clinmedicine.17-4-350
|View full text |Cite
|
Sign up to set email alerts
|

Acute geriatrics at the front door

Abstract: Older people with frailty and urgent care needs are major uses of health and social care services. Comprehensive geriatric assessment (CGA) is an evidence-based approach to improving their outcomes, as well as improving service outcomes. Geriatricians form a small proportion of the overall workforce and cannot address the population need alone, so all clinicians (doctors, nurses, therapists and so on) need to engage in delivering CGA as a process of care, underpinned by specifi c competencies -which can be dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…However, how to identify the patients in need of geriatric assessment remains unclear. Using frailty scales as risk stratification tools might be a possibility 54 55. Several frailty rating scales exist19 and screening appears to predict the risk of mortality,56 length of admission57 and risk of readmission57 depending on the frailty scale used.…”
Section: Discussionmentioning
confidence: 99%
“…However, how to identify the patients in need of geriatric assessment remains unclear. Using frailty scales as risk stratification tools might be a possibility 54 55. Several frailty rating scales exist19 and screening appears to predict the risk of mortality,56 length of admission57 and risk of readmission57 depending on the frailty scale used.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 22% of the global population will be aged ≥65 years by 2050 . Older frail people and those with urgent care needs are major users of health and social care services . Criteria to identify inappropriate medication for older people have been developed in North America, Europe and Asia .…”
Section: Introductionmentioning
confidence: 99%
“…1 Older frail people and those with urgent care needs are major users of health and social care services. 2 Criteria to identify inappropriate medication for older people have been developed in North America, Europe and Asia. 3 Azoulay et al 4 evaluated prescriptions from 3000 elderly patient visits in Isfahan, Iran, and reported that 27.6% of geriatric patients recorded at least one potentially inappropriate medication (PIM).…”
Section: Introductionmentioning
confidence: 99%
“…EDIFY was designed for the dual purpose of reducing the number of potentially avoidable acute admissions and delivering interprofessional geriatric interventions through comprehensive geriatric assessments, and promoting awareness and education on frailty. 2,3 The program significantly reduced acute admissions without escalating the risk of rehospitalization, ED re-attendance, or mortality. 1 We conducted a survey among ED staff aimed at assessing their perceptions of knowledge and confidence in managing older persons and to explore their satisfaction with current geriatric expert This work was supported by the Ng Teng Fong Healthcare Innovation Programme (Project Code: NTF_JUL2017_I_C2_CQR_02), National Healthcare Group, Singapore, which had no role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript.…”
mentioning
confidence: 99%
“…Because of time pressures at the ED, addressing complex multidimensional needs of older persons often do not take precedence. 2,3 Hence, care models designed specifically to deliver frailty-centric care at the ED are needed to improve functional outcomes and reduce ED re-attendance among older persons. 1,4e7 Our study had a number of limitations.…”
mentioning
confidence: 99%